Microstructure and tensile properties of nanocrystalline (FeNiCoCu)1−xTixAlx high entropy alloys processed by high pressure torsion. (July 2016) - Zheng, Ruixiao; Chen, Jing; Xiao, Wenlong; Ma, Chaoli
Abstract: In this study, an equal-atomic FeNiCoCu high entropy alloy (HEA) and a Ti and Al added (FeNiCoCu)86 Ti7 Al7 HEA were subjected for high pressure torsion (HPT) up to 10 rotations. Microstructure observation and mechanical properties test revealed that significant grain refinement as well as enhanced strength could be obtained in both HPT processed alloys. The HPT processed FeNiCoCu HEA alloy shows nanocrystalline structure consisting of FCC matrix (grain size ∼100 nm) and FeCo-riched BCC phase. The HPT processed (FeNiCoCu)86 Ti7 Al7 HEA alloy shows nanocrystalline structured FCC matrix (mean grain size ∼50 nm) and refined NiCoTiAl-riched particles (mean particle size ∼0.71 μm). The ultimate tensile strength of the HPT processed FeNiCoCu and (FeNiCoCu)86 Ti7 Al7 alloys are 1402 MPa and 1849 MPa, respectively. The microstructure evolution during HPT and strengthening mechanisms of the HPT processed specimens were discussed. Highlights: Nanocrystalline (FeNiCoCu)1−x Tix Alx HEAs can be prepared by high pressure torsion. The HPT FeNiCoCu HEA has a high tensile strength and a high ductility. Minor Ti and Al additions significantly strengthen the as-cast and HPT alloys.